Life Efforts Online: E-commerce Entrepreneurship and Platform-based Governance in Rural China - Wang, Weijing (Journal of Political Sociology, 2025)
This article explores how people work as e-commerce entrepreneurs under the control of platforms and the blueprint of rural development laid out by China’s central government. It asks: through what mechanisms do the state and the platform govern rural e-commerce entrepreneurs to achieve their economic and political goals? And how the unprecedented scale of e-commerce in rural China has reshaped local communities and people’s lives? It argues that the popularization of e-commerce in rural China is encouraged by the partnership of state and Chinese platform giants as a public-private alliance. Rural e-commerce entrepreneurs are aspiring to be their own bosses, nonetheless, they are in “the digital cage” where work and life get blurred in the social domain. The family-based online entrepreneurship in rural China contributes to China’s future developmental mode from the grassroots.